2016
DOI: 10.1007/s00397-016-0951-6
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterization of triglyceride shortenings

Abstract: The rheological properties of shortenings with similar physicochemical characteristics but diverse functionality were investigated under small and large oscillatory shear. Particular attention was drawn to the mechanical behavior of roll-in shortenings, characterized for resisting work softening and forming continuous fat thin films during dough lamination and sheeting. All shortenings displayed low-frequency dependence, reminiscent of viscoelastic solids where the storage modulus is higher than the loss modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 51 publications
3
12
0
Order By: Relevance
“…CM101 had the highest G ′ and G ″ over the frequency range, which could be related to its SFA content and SFC ( P < 0.05). This was in line with Macias‐Rodriguez and Marangoni () results of analyzing the rheological characterization of triglyceride shortenings. They showed that shortenings with higher saturated fats had a higher G ′.…”
Section: Resultssupporting
confidence: 91%
“…CM101 had the highest G ′ and G ″ over the frequency range, which could be related to its SFA content and SFC ( P < 0.05). This was in line with Macias‐Rodriguez and Marangoni () results of analyzing the rheological characterization of triglyceride shortenings. They showed that shortenings with higher saturated fats had a higher G ′.…”
Section: Resultssupporting
confidence: 91%
“…, in all oleogels and commercial shortening, both G ′ and G ″ slightly enhanced parallel with enhancing frequency in which G′ value predominated over the whole frequency range, demonstrating the gel‐like characteristic of these systems. A similar trend was also observed for oleogels of carnauba wax (CRW) and candelilla wax (CDW) as a shortening replacer as well as for some commercial shortening in previous studies (Macias‐Rodriguez and Marangoni, ; Mert and Demirkesen, ). The Bohlin model with R 2 of 0.96 fitted the dependency of G ′ on frequency (data not shown).…”
Section: Resultssupporting
confidence: 83%
“…Since we observed that multiple formulations (e.g. palm‐oil based, soybean‐oil based, trans ‐containing, trans ‐free) achieved the same rheological criteria, the structure‐function framework seemed to dictate the unique laminating performance .…”
Section: Case Study: Rationalizing the Functionality Of Laminating Shmentioning
confidence: 99%
“…The remaining question then arises: what rheological characteristics a shortening must meet to achieve the special laminating functionality? To address this, we present LAOS results, which are related to the macroscopic functionality of laminating shortenings [4,5]. Figure 1a shows strain softening as the strain amplitude is increased; however, the response is otherwise unremarkable, that is both shortenings behave as soft elastic solids (G' > G").…”
Section: A Case Study: Rationalizing the Functionality Of Laminating mentioning
confidence: 99%
See 1 more Smart Citation